The degree of cycle irregularity correlates with the grade of endocrine and metabolic disorders in PCOS patients - Strowitzki, Thomas; Capp, Edison; Corleta, Helena von Eye (European journal of obstetrics & gynecology and reproductive biology, 2010)
Objective - PCOS (polycystic ovarian syndrome) is a clinically heterogeneous endocrine disorder which affects up to 4-10% of women of reproductive age. A standardized definition is still difficult because of a huge variety of different phenotypes. The aim of this study was to evaluate possible correlations between the degree of cycle irregularity and the grade of endocrine and metabolic abnormalities. - Study design - A cross-sectional study was carried out. Hyperandrogenic and/or hirsute women with regular menstrual cycles and polycystic ovaries on ultrasound (PCOS eumenorr, n=45), PCOS patients with oligomenorrhea (PCOS oligo, n=42) and PCOS patients with amenorrhea (PCOS amenorr, n=31) were recruited from the Department of Gynecological Endocrinology and Reproductive Medicine of the Women's University Hospital Heidelberg (Heidelberg, Germany). - Results - Normocyclic patients demonstrated significantly better metabolic parameters (BMI, fasting insulin, HOMA-IR) than patients with oligo/amenorrhea. Hormonal parameters (LH, FSH, FAI and testosterone) were significantly different between patients with different menstrual patterns and patients with regular cycles. - Conclusion - Determining the degree of cycle irregularity as a simple clinical parameter might be a valuable instrument to estimate the degree of metabolic and endocrine disorders. Emphasis should be given to those parameters as a first step to characterize PCOS patients with a risk of endocrine and metabolic disorders leading to consequent detailed examination.
Gesehen am 01.09.2023